2018
DOI: 10.1007/s00380-018-1242-1
|View full text |Cite
|
Sign up to set email alerts
|

Aortic root dilatation in patients with mucopolysaccharidoses and the impact of enzyme replacement therapy

Abstract: Mucopolysaccharidoses (MPS) are disorders characterized by impaired glycosaminoglycan (GAG) catabolism as a consequence of a deficiency or the absence of lysosomal enzymes directly involved in their degradation. Multiple organ systems are involved in MPS, including the cardiovascular system. Recently, aortic root dilatation (ARD) has been described in these patients. Thus, we reviewed aortic root diameter measurements in 69 MPS patients from a single center from 2000 to 2016. Aortic root diameter z scores were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
4
16
1
Order By: Relevance
“…In our cohort, there was no significantly higher incidence of ARD at the SoV compared to controls. In contrast, two recent publication reported a higher incidence of ARD in MPS patients, respectively in 39.1% and 35% . However, Poswar et al did not include any MPS III patients in their study, and Bolourchi et al reported the same mean ARD at the SoV in 6 MPS III patients as we report in our patients.…”
Section: Discussioncontrasting
confidence: 79%
“…In our cohort, there was no significantly higher incidence of ARD at the SoV compared to controls. In contrast, two recent publication reported a higher incidence of ARD in MPS patients, respectively in 39.1% and 35% . However, Poswar et al did not include any MPS III patients in their study, and Bolourchi et al reported the same mean ARD at the SoV in 6 MPS III patients as we report in our patients.…”
Section: Discussioncontrasting
confidence: 79%
“…AHI and OSAs, when evaluated, seem to be reduced by ERT, but it is clear that macroglossia and adeno-tonsils hypertrophy are not modified during long-term treatment [36,45,46,49,50,[61][62][63][64]. Although only few cases are reported, it appears that ERTs do not act on deformities of trachea, bronchi and vessels [65][66][67][68][81][82][83][84]. In the first years after ERT availability it seemed that it could have a "stabilization" role on hearing loss and corneal clouding but unfortunately the different articles do not agree on this point and the final impression is that hearing and eyes are among the difficult-to-reach targets for ERT [42,47,59,60,[85][86][87][88][89][90].…”
Section: Discussionmentioning
confidence: 99%
“…An increase of thickness was found in all the MPS patients at all ages [81]. Aortic root dilatation was recently evaluated in two different papers that showed a prevalence ≥ 35% in all MPS types with the highest occurrence in MPS IVA and MPS VI patients (>70%) [80,82]. Other studies underline the vulnerability of the cardiovascular system in MPS and especially in MPS IVA [145,146].…”
Section: Vesselsmentioning
confidence: 97%
“…Patients usually develop a progressive thickening of the cardiac valve leaflets, resulting in valvular insufficiency and/or stenosis, predominantly in the mitral and aortic valves [18]. Cardiovascular manifestations may also include left ventricle hypertrophy, systemic or pulmonary hypertension, coronary artery disease, and aortic root dilatation [19][20][21].…”
Section: Severe Phenotype (Hurler Syndrome)mentioning
confidence: 99%